Development of three dimensional volumetric rendering in medical image application / Wu Danping - Wu, Danping (2021)
The distribution, area size, shape, direction, and spatial structure of bones,surface skin, blood vessels and other tissues or organs are the key basis of reference for clinical treatment, diagnosis, and prognosis. On the one hand, due to the continuous development for a long time, the traditional medical images has its unique advantages as the main clinical examination method. On the other hand, the shortcomings of two dimensional (2D) medical images are also obvious: (1). it is difficult for non-professionals to understand complex medical images, which increases the difficulty of doctor-patient communication and treatment. (2). the tissue and organ structure itself is very complex, even experienced professionals will experience misdiagnosis or missed diagnosis due to various factors. (3). there are few professionals with rich practical experience. Compared with 2D medical images, Three-dimensional (3D) reconstruction medical image is a more clinically practical technical method, the reconstructed image can intuitively display tissues or organs from all directions of point, line and plane. The Visualization Toolkit (VTK) is an excellent and powerful open source software that encapsulates many class libraries to facilitate the realization of 2D to 3D image reconstruction. It is very suitable for use by researchers. This paper first analyzes the imaging principles and its limitation of CT, MRI, and ultrasound 2D images, at the same time briefly describe the DICOM medical image standard, the class objects/libraries needed to read DICOM image files in VTK, and the specific implementation steps. Then, introduced the process of 3D volumetric rendering and C++ code on the VTK and visual studio 2008 platform in detail, and focuses on the explanation of the VTK functions that affect the 3D volumetric rendering effect. Next, 3D volumetric rendering is performed using realistic CT brain/head, MRI brain, and ultrasound fetal phantom slices data. Three kinds of medical images were evaluated directly according to the obtained 3D volumetric rendering results, an objective analysis of the 3D volumetric rendering and their corresponding 2D image, as well as the comparison between the three different types of images. The findings of 3D volumetric rendering in three medical image applications are summarized. Finally, in Chapter 5, the development of 3D volumetric rendering in medical images will be discussed in detail.